(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The chemical features of 1,3,4-thiadiazoles were described in a numerous reviews focusing on the main approaches to the synthesis and modification. Heterocyclic compounds occupy a central position among those molecule that makes life possible. Among of these compounds having 1,3,4,-thiadiazole nucleus are known to exhibit unique antiinflammatory, analgesic, antimicrobial, antitumor, antifungal, antimycobacterial, anticonvulsant, antidiabetic, antiviral, activities. The significant biological activity of thiadiazolederivates promotes the scientists to further investigation of this heterocycle as a building block for medicinal chemistry. The present review highlights the recently synthesized thiadiazole possessing important biological activities.